The recent evolution of retirement patterns in Canada - Pierre Lefebvre; Philip Merrigan; Pierre-Carl Michaud (Institute for the Study of Labor (IZA), 2011)
Using data from three waves of the General Social Survey on retirement and older workers (1994, 2002 and 2007), we document the evolution of retirement patterns over the last three decades. We combined the analysis of retirement ages of actual retirees with data on expected retirement ages of current workers to create a longer perspective on changes in retirement behaviour in Canada. We also investigate trends in work after retirement. Our findings are in line with findings from other countries. There is an upward trend in retirement ages which likely started around year 2000 for cohorts born after 1945. This trend contrasts with the slow decline in retirement ages observed prior to the end of the millennium. While the downward trend was likely due to factors such as the offering of early retirement programs in private firms, the upward trend is likely to be caused by a wider variety of sources, including better health, less pervasive defined benefit pensions and in general less generous pensions.
urn:nbn:de:101:1-201110102404
Keywords: J26; 330; retirement; pensions; Canada; Altersgrenze; Altersgruppe; Gesetzliche Rentenversicherung; Kanada